2004
DOI: 10.1128/jb.186.3.699-705.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IcsP, the Outer Membrane Protease of the Shigella Actin Tail Assembly Protein IcsA, by Virulence Plasmid Regulators VirF and VirB

Abstract: The Shigella outer membrane protease IcsP removes the actin assembly protein IcsA from the bacterial surface, and consequently modulates Shigella actin-based motility and cell-to-cell spread. Here, we demonstrate that IcsP expression is undetectable in mutants lacking either of two transcriptional activators, VirF and VirB. In wild-type Shigella spp., virB expression is entirely dependent on VirF; therefore, to circumvent this regulatory cascade, we independently expressed VirF or VirB in Shigella strains lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 39 publications
5
102
0
Order By: Relevance
“…Our previous studies at the icsP and ospZ locus have revealed that H-NS is able to repress the icsP promoter at 37°C (14). Therefore, we hypothesized that H-NS would also repress transcription of the divergent gene ospZ at 37°C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies at the icsP and ospZ locus have revealed that H-NS is able to repress the icsP promoter at 37°C (14). Therefore, we hypothesized that H-NS would also repress transcription of the divergent gene ospZ at 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…Upon a switch to 37°C, a complex regulatory cascade is triggered, which results in the production of VirF and subsequently VirB (3,24,25). Although some virulence genes are derepressed solely by the increase in temperature (23), others are derepressed at 37°C by either VirF or VirB, which function to relieve the H-NS-mediated repression of these virulence gene promoters on the large virulence plasmid (3,14,21,26).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…icsP is also regulated by the H-NS antagonist VirB. 114 icsA is expressed upon invasion of the host through its regulators H-NS, VirF and a 450 nt antisense RNA (RnaG) acting as transcriptional attenuator. H-NS was shown to repress icsA transcription at 30°C but not at 37°C.…”
Section: Do Not Distributementioning
confidence: 99%